Testimony and revolution. An analysis of the novel La montaña es más que una inmensa estepa verde by Omar Cabezas - Astorga Sánchez, Leonardo (2022)
The present paper aims to analyze the way in which testimonial literature was a key element in the process of legitimizing revolutionary governments, for this reason, the case of the novel published by Omar Cabezas, a former Sandinista guerrilla, which was published during the years in which the government of the Sandinista National Liberation Front carried out its project during the 1980s. Likewise, the analysis starts from the fact that every revolution seeks to create new ways of doing and seeing the world, literature being one of the fields where such effort is carried out. Finally, the role played by youth in a context of radicalization during the Cold War is highlighted.